Contemporary Still Life. - The Renaissance Society at the University of Chicago (Chicago : The Renaissance Society at The University of Chicago, 1974)
Alvarez, Maria Luisa ; Asdell, Paul ; Barnes, Robert ; Beal, Jack ; Beuys, Joseph ; Botero, Fernand ; Caponigro, Paul ; Clarke, John Clem ; Dine, Jim ; etc.
Contemporary Still Life, The Renaissance Society at The University of Chicago, October 6-26, 1974
boek